Construction and optimization of an electrochemical genosensor for the detection of BDNF gene Val66Met polymorphism - Caldevilla, Renato (2023)
Major depression disorder (MDD) is the most prevalent psychiatric condition worldwide. Currently, antidepressants constitute the main pharmacological treatment for this condition. Despite the growing arsenal of antidepressant medications, almost half of MDD patients have insufficient remission rates during their treatments. A growing body of scientific evidence points to genetic factors as having a crucial role in patients’ response to antidepressant treatments. One of these genetic components is the BDNF gene, that codes for the BDNF neurotrophin, an important player in neuroplasticity and neurogenesis.